Samahan ng Tatlong Persona Solo Dios an ethnography of religious conversion - Kuwada, Reiko (2007)
Mt. Banahaw is considered a sacred place by many Filipinos. Many religious sodalities like the Ciudad Mistica de Dios, the Iglesia Watawat ng Lahi and the Benevolent Brothers have established their churches along the slopes of the mountain. Previous ethnographies have described and analyzed the organizational structure, the beliefs and religious practices of these groups. They have also offered various theoretical explanations to account for their emergence at certain periods in the history of the country. A gap in these studies is the lack of empirical data derived from the voices and narratives of the members themselves about their reasons for joining and how they have constituted and reconstituted their identities as they shifted from one religious orientation to another. This study addresses this gap. It attempts to describe and analyze the processes of conversion by the members of the Samahan ng Tatlong Persona Solo Dios, a religious group that was founded in the 1920s and now claims to have around 13,000 members throughout the country. This study also examines how the members reconstitute their identities from a location of being an outsider, to being a new convert and eventually, a regular member...